Knowledge, attitude and practice of contraception complications among hospitalized women following self-induced medical abortion at tertiary hospital - Pal, Aparajita; Baidya, Jahar Lal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Unwanted pregnancies in women and complications of induced abortions are an important health problem in the world. There is recent trend of self-induced medical abortion pill use over the counter without knowing the recommendations. Objectives of this study were to study socio demographic profile, presentations, management of hospitalized women for medical abortion related complications. To explore out contraceptive practices in those women. To way out the reasons for choosing medical abortion by women. Methods: Women of reproductive age group (15-45 years) who admitted in department of Obstetrics and Gynaecology Medical College with the complications following self-induced medical abortion were enrolled. Patients’ demographic profile, socio-economic status, obstetric profile, KAP of contraception, logical reasons for self-induced abortion were studied. Management of each case was done according to hospital protocols. Results: The total number of patients that were enrolled for the study period was 100. 37% of hospitalized women were between 18-25 years age group and 45 % of them had marriage at early age (15-20 years) and 46% were belonged to lower middle-class group. Majority of women with single living child with their last child <1-year age had taken abortion pills for unplanned pregnancy (49%). 74% women had taken abortion pills over the counter for the first time and 88% women did have idea about contraception but never used. 70% of the women had to undergo surgical evacuation and six of them had undergone emergency laparotomy for ruptured tubal ectopic pregnancy. Post abortion counselling successfully convinced to accept combined oral contraceptive (31%), followed by IUCD and permanent sterilization and 16% of women by medical abortion pill refused to accept contraception. Conclusions: Pregnancy termination should be done by qualified medical personal with accurate information about safe medical abortion. Counselling of each couple is must to enhance continuous and consistent use of family planning methods.